The use of sliding modes to simplify the backstepping control method - Stotsky, Alexander A.; Hedrick, J. Karl; Yip, P.P. (Zielona Góra: Uniwersytet Zielonogórski)
A simple sliding mode based controller for nonlinear systems with mismatched uncertainties is proposed. The design methodology is similar to a backstepping and multiple surface control method, but with the inclusion of sliding mode filters for estimating the derivatives of the plant output.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka